SEPARATION OF HYDROCARBON FLUID AND WATER IN AN ELASTIC WAVE FIELD ACTING ON A POROUS RESERVOIR MEDIUM - Pogosyan A.B.; Simkin E.M.; Stremovskiy E.V.; Surguyev M.L.; Shnirel'man A.I. (My University, 1989)
The paper reports on studies that used models prepared by cementing a mixture of loose porous Lyuberets quartz sand and marshallite with an alcohol solution of BF-2 glue, then drying it with hot nitrogen. This procedure yielded a model 1 m long and 0.03 m in diameter with a permeability of 5.4·10-12 m2 and a porosity of 0.33. The model was filled with a mixture of saline water (5 percent NaCl) and kerosene by the following procedure: it was first saturated with water, which was then displaced with kerosene, which in turn was again displaced with water. The water content of the model when in vertical position was determined by measuring its resistivity. Study methods and results are discussed.